Study of the Characteristics of Suweg (Amorphophallus campanulatus Blume ex Decne) Tuber Flour Through Preliminary Treatment - Ana Agustina; Adinda Fajriati Nur Hasanah; Aprilia Dwi Rahmawati; Diajeng Rahma Febriana; Dina Sukma Sari; Yesinta Mariana Rahmawati (Universitas Muhammadiyah Palembang, 2024)
Suweg tubers are the primary source of carbohydrates due to their substantial carbohydrate content. In addition, suweg tubers are rich in fiber, vitamins, and minerals, all of which are advantageous to one's health. Nevertheless, suweg tubers also contain calcium oxalate, which can result in itching and can even cause problems with kidney health. Aim of this investigation is to determine the chemical characteristics (macro nutrients) of suweg tuber flour through pretreatment with HCl and salt solutions. The calcium oxalate content of suweg tubers was reduced by administering an immersion treatment with a 0.25% hydrochloric acid (HCl) solution and a salt solution in this study. The research results indicate that the characteristics of suweg tuber flour differ between the two treatment methods. The information on water content, ash content, protein, fat, carbohydrates, and crude fiber in suweg tuber flour with salt soaking treatment is as follows: 5.53%, 5.66%, 7.56%, 0.67%, 77.69%, and 2.88%, respectively. In the meantime, the data on suweg tuber flour that was treated with a 0.25% HCl solution were as follows: 9.03%, 4.92%, 7.13%, 0.42%, 71.96%, and 6.54%. Suweg tuber flour has the potential to serve as an alternative carbohydrate source. This research establishes a foundation for the continued exploration of suweg tubers as a food ingredient with exceptional nutritional value. It is anticipated that this research will enhance comprehension of the potential of suweg tubers as a high-value food source and facilitate Indonesia's food diversification program.